Opportunities and Challenges Posed by International Trade on Agriculture in Developing Nations: A Review - A. S. Famuyiwa (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to review the opportunities and challenges posed by international trade on agriculture in developing nations by harvesting information and data from online and library sources. The review highlights the key benefits of trade, including expanded market access, economic development, and technology transfer, which enhance agricultural productivity and global food security. Countries engaged in agricultural trade benefit from diverse markets, improved access to modern farming technologies, and increased export revenues. However, challenges such as trade barriers, price volatility, environmental sustainability concerns, and the vulnerability of smallholder farmers persist. The review underscores the importance of balanced trade policies that promote equitable benefits, protect local agricultural sectors, and encourage sustainable farming practices. It also calls for further research to evaluate the long-term impacts of trade agreements on local agricultural systems and foster international cooperation to address shared challenges. Overall, the review argues for policies that enhance the resilience and inclusiveness of agricultural trade while ensuring sustainability for future generations.